“Geopolitics Theory” Cannot Serve as a Methodology for Analyzing International Relations and the International Situation: An Interview with Zhou Li, Former Vice Minister of the International Department of the Central Committee of the Communist Party of China (World Marxist Review, 2025)
In recent years, an increasing number of scholars and political figures both at home and abroad have embraced geopolitics theory, deeming it a crucial constituent of contemporary international relations theory and an instrument for observing and analyzing the current state and future trends of the international situation. This theory has exerted significant influence on the international community for over a century. The essence of geopolitics lies in the fact that geography determines politics, and the geographic environment dictates international relations. It can be asserted that representatives of Western countries in different historical periods have assiduously advocated geopolitics theory. No matter how convoluted or “deep” their arguments may seem, ultimately, they are designed to assist Western powers in seizing more colonies, spheres of influence, sources of raw materials and investment opportunities. It facilitates their advancement of neo-colonialism, fascism and hegemonism throughout the world. Indisputably, geopolitics theory is a direct reflection of imperialist and hegemonic worldviews. It is also true that Chinese Communists, when observing and analyzing any international phenomenon, be it political, economic, ecological, security-related or related to hotspots, must adhere to the Marxist perspective and method of class and class analysis, as well as the viewpoint and methodology that the contradiction between productive forces and relations of production is the decisive force in social development. It is definitely not possible to use geopolitics theory as the logical starting point for analyzing international relations and the evolution of the international situation, or even as a methodological framework for analyzing issues. The reason is that this would result in misjudgments on the development and changes in the international situation, and thus influencing the formulation and implementation of specific policies. Chinese foreign relations theory is constructed on Marxist international relations theory and constitutes an essential underpinning of the confidence in socialist theory with Chinese characteristics in the new era. There is no doubt that it should be included and developed as a prominent ingredient of China’s independent knowledge system.